2021
DOI: 10.3389/fsurg.2021.690680
|View full text |Cite
|
Sign up to set email alerts
|

Survey Fatigue During the COVID-19 Pandemic: An Analysis of Neurosurgery Survey Response Rates

Abstract: Background: The COVID-19 pandemic has caused a surge in research activity while restricting data collection methods, leading to a rise in survey-based studies. Anecdotal evidence suggests this increase in neurosurgical survey dissemination has led to a phenomenon of survey fatigue, characterized by decreased response rates and reducing the quality of data. This paper aims to analyze the effect of COVID-19 on neurosurgery surveys and their response rates, and suggest strategies for improving survey data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(141 citation statements)
references
References 25 publications
5
112
1
Order By: Relevance
“…Although the study had a large sample size, the response rate was relatively low in the Australian health services. Nevertheless, the response rate is similar to that of other studies conducted during an infectious disease outbreak ( Maunder et al, 2004 ); and it has been suggested that survey-based studies among healthcare workers have had lower response rates during the COVID-19 pandemic than prior to the pandemic (34.5% vs. 51.0%, p<0.001) ( de Koning et al, 2021 ). It was also not possible to determine the number of nurses and midwives who received the email invitation to complete the survey.…”
Section: Discussionsupporting
confidence: 76%
“…Although the study had a large sample size, the response rate was relatively low in the Australian health services. Nevertheless, the response rate is similar to that of other studies conducted during an infectious disease outbreak ( Maunder et al, 2004 ); and it has been suggested that survey-based studies among healthcare workers have had lower response rates during the COVID-19 pandemic than prior to the pandemic (34.5% vs. 51.0%, p<0.001) ( de Koning et al, 2021 ). It was also not possible to determine the number of nurses and midwives who received the email invitation to complete the survey.…”
Section: Discussionsupporting
confidence: 76%
“…The low response rates highlighted a possible lack of interest in participating in the study in a tragic and unexpected historical period such as the pandemic, which has led to an upheaval in family and work habits; the length of the survey; the absence of certainty of protection of privacy and confidentiality are all factors. As described in a previous study [ 31 ], the COVID-19 pandemic has led to survey fatigue characterized by non-response, with a consequent decrease of response rate during the pandemic. This could be explained by the fact that during the COVID-19 pandemic, the number of surveys created and disseminated has increased significantly with the consequence that HCWs may feel overwhelmed with the number of survey requests, also due to the great increase in social media dissemination during the COVID-19 pandemic that can contribute to the illusion that survey requests are omnipresent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we had a modest response rate. This appears to be a relatively frequent issue for online surveys, and it is possible that it might have been exacerbated by the pandemic [43,44]. While it could be postulated that the characteristics of this population may have also contributed to the low response rate, current studies evaluating survey responses among sexual minorities do not support this assumption [45].…”
Section: Discussionmentioning
confidence: 89%